The complete mitogenome of Lasioglossum affine (Hymenoptera: Halictidae) and phylogenetic analysis - Jinyi Wei; Huanhuan Lu; Jingxin Tao; Youjin Hao; Dunyuan Huang; Bo Li (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitogenome of Lasioglossum affine (Hymenoptera: Halictidae) was sequenced and analyzed. The whole mitogenome is 17,352 bp (AT%=84.1%) and encodes 37 typical eukaryotic mitochondrial genes, including 13 protein-coding genes (PCGs), 22 tRNAs, two rRNAs, and an AT-rich region. Further analysis found three gene rearrangements, where trn I-Q-M → trn M-I-Q, trn W-C-Y → trn C-W-Y, and trn K-D → trn D-K were shuffled. The phylogenetic relationships of 19 species of Hymenoptera were established using maximum-likelihood method based on 13 concatenated PCGs. The result showed that Lasioglossum affine is a sister of Lasioglossum sp. SJW-2017.